Decisions for Others Are Less Risk-Averse in the Gain Frame and Less Risk-Seeking in the Loss Frame Than Decisions for the Self - Zhang, Xiangyi; Liu, Yi; Chen, Xiyou; Shang, Xuesong; Liu, Yongfang (Frontiers in Psychology, 2017)
Despite the fact that people make decisions for others as often as they make decisions for themselves, little is known about how decisions for others are different from those made for the self. In two experiments, we investigated the effect of social distance (i.e., making decisions for oneself, a friend, or a stranger) on risk preferences in both gain and loss situations. We found that people were more risk averse in gain situations when they made decisions for themselves than for a stranger (Studies 1 and 2), but were equally risk averse for themselves and their friends (Study 2). However, people were more risk seeking in loss situations when they made decisions for themselves than for their friends as well as for a stranger, and were more risk seeking for their friends than for a stranger (Study 2). Furthermore, the effect of social distance on risk preferences was stronger in loss than in gain situations. Mediation analysis indicated that outcome-induced loss aversion was responsible for effects of social distance on risk preferences. These findings demonstrate that social distance influences risk preferences via perceived loss aversion, which sheds new light on self-other differences in decision making.